2018
DOI: 10.1007/s12038-018-9759-0
|View full text |Cite
|
Sign up to set email alerts
|

A parasporin from Bacillus thuringiensis native to Peninsular India induces apoptosis in cancer cells through intrinsic pathway

Abstract: Parasporins, a class of non-insecticidal crystal proteins of Bacillus thuringiensis (Bt) are being explored as promising anticancer agents due to their specific toxicity to cancer cells. The present study has identified 25 Bt isolates harbouring parasporin genes from Western Ghats region, the hotspot of biodiversity in India. Among these, the isolate, KAU 41 (Kerala Agricultural University isolate 41) contained non-hemolytic homogenous crystals showing specific cytotoxicity towards cancer cells. SDS-PAGE analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…Many countries including Saudi Arabia (our research team) are continuing to screen and isolate novel strains in natural environments to apply for biological pest management programs whereby reducing insect resistance to Bt [12,20,21,22,23]. Moreover, global efforts are currently being intensified towards the discovery of local Bt isolates with unique anticancer properties [13,19,24,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Many countries including Saudi Arabia (our research team) are continuing to screen and isolate novel strains in natural environments to apply for biological pest management programs whereby reducing insect resistance to Bt [12,20,21,22,23]. Moreover, global efforts are currently being intensified towards the discovery of local Bt isolates with unique anticancer properties [13,19,24,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Maher [ 19 ] identified two strains J61 and J72, with cytotoxic activity against MCF-7 that reduce to 50% cell viability at 1 µg/mL and 2.79 µg/mL, respectively. Other authors tested differents parasporins observing no significant cytotoxic activity against MCF-7 [ 20 , 21 , 22 ]. It has been reported that a parasporin could affect more than one cancer line of cells.…”
Section: Discussionmentioning
confidence: 99%
“…First, using recombinant proteins, the hemolytic activity of Glabralysins will be investigated, and then their cytotoxic/cytolytic effects on micro-organisms or pathogens will be analyzed, as was done for Biomphalysin [25]. Moreover, as some the members of the Bt β-PFT family (the parasporins) have selective against specific human tumor cell lines [90,[93][94][95][96][97], any possible anticancer activity of Glabralysins will be investigated, and any molecules showing a positive activity can be considered as potential new chemotherapeutic drugs [98][99][100].…”
Section: Discussionmentioning
confidence: 99%